An inherited gain‐of‐function risk allele in EPOR predisposes to familial JAK2V617F myeloproliferative neoplasms. (30th March 2022) - Rabadan Moraes, Graciela; Pasquier, Florence; Marzac, Christophe; Deconinck, Eric; Damanti, Carlotta Caterina; Leroy, Gwendoline; El‐Khoury, Mira; El Nemer, Wassim; Kiladjian, Jean‐Jacques; Raslova, Hana; Najman, Albert; Vainchenker, William; et al.
Summary: Myeloproliferative neoplasms (MPN) are mainly sporadic but inherited variants have been associated with higher risk development. Here, we identified an EPOR variant ( EPOR P488S ) in a large family diagnosed with JAK2 V617F ‐positive polycythaemia vera (PV) or essential thrombocytosis (ET). We investigated its functional impact on JAK2 V617F clonal amplification in patients and found that the variant allele fraction (VAF) was low in PV progenitors but increase strongly in mature cells. Moreover, we observed that EPOR P488S alone induced a constitutive phosphorylation of STAT5 in cell lines or primary cells. Overall, this study points for searching inherited‐risk alleles affecting the JAK2/STAT pathway in MPN.